Review of microfluidic microbial fuel cell technology - Chun, Shi Kang (2016)
Microbial fuel cell (MFC) is a novel technology that utilizes the power of respiring microorganism to convert chemical energy stored in organic substrates directly into electrical energy. MFC hold great promise as an alternative method of energy production but currently widespread use of MFC for real-world applications is not possible due to its low power density. Recently, microfluidic MFCs or microscale MFCs has gain the interest of researchers due to its potential applications as a portable power source, biosensors and as a research tool for the development of MFC technology. This master dissertation is to provide a review of the development and fundamentals of MFC technology in general and to summarize the development, challenges, potential applications and the future outlook of microscale MFCs.